Why mentor? Linking mentor teachers' motivations to their mentoring conceptions. Issue 1 (2nd January 2016) - van Ginkel, Gisbert; Verloop, Nico; Denessen, Eddie
Abstract : Current mentoring models for teacher preparation and induction emphasize the need to engage novice teachers' learning through collaborative professional learning communities. Mentors in such communities are expected to engage in joint knowledge construction with novices, and to be 'co-thinkers' who enact a developmental view of mentoring, as well as 'co-learners' who are willing to engage in mutual learning with their novices. These two aspects are assumed to be associated in mentor thinking. The aim of this questionnaire study was, therefore, to explore the relationship between mentors' mentoring conceptions and their mentoring motives. Participants were 726 secondary education mentor teachers, associated with 13 institutes for teacher preparation in the Netherlands. Results showed that a motivation to mentor for personal learning was more strongly associated with a developmental conception of mentored learning to teach than with an instrumental mentoring conception. The same was found for a motivation to mentor for contributing to the profession, but less pronounced. These findings suggest potential strategies for the selection and preparation of mentor teachers for programs that intend to foster collaborative inquiry approaches for novice teacher support.